The WhatsApp Profile Photo: Identity Representation and Visual Rhetoric in the Digital Age - Udo, Nsima Stanislaus (WritingThreeSixty, 2018)
The convergence of the camera and the phone has changed the way images are produced, appropriated and circulated. According to Mikko Villi, camera phone has shifted image accessibility and consumption f rom a future anticipation to a near real-time connection. With internet facilities on a camera phone, images can be transmitted almost synchronously between the sender and the receiver.1 Photographs through the camera phone are able to transmit information to receivers which was intended by the sender in the form of ―visual language‖. This essay examines ―the social life [and agency] of photos‖2 and how images used as WhatsApp profile reflect and bear witness to events, identity, people, experience and individual conceptions not recorded in words. Do images ―write our past‖? Do they represent our feeling, our emotions and our sentiments? Does the image we choose to post as the WhatsApp profile reflect our philosophical and ideological standpoint? How do images as used on contemporary social media and messaging applications as status or identity profile reflect and evoke our identity? The essay tries to argue that though WhatsApp profile images are meant to authenticate the identity of the users behind the chat on both sides, these images also describe and illustrate important social and psychological details about the users in visual form. Thus, while images are meant to act as profile, they exude more of individual Identity representation, as well as a form of visual rhetoric in the digital age.